EFEK HIPOGLIKEMIK INFUSA DAUN TANAMAN MAKASAR, Brucea javanica (L) Merr, PADA TIKUS HIPERGLIKEMIK YANG DIINDUKSI ALOKSAN - Handa Muliasari; Candra Dwipayana Hamdin; Muhsinul Ihsan (Scripta Biologica, 2017)
Brucea javanica (L) Merr is a local plant used traditionally for diabetic medication in Lombok Island. The B. javanica seed has been recognized to have an antidiabetic effect, while the impact of the leave extract was understudied. The purpose of this research was to determine the effect of B. javanica leaves infusion on the blood glucose level of alloxan-induced diabetic rats. B. javanica leaves extract were applied by soaking leaves into hot water (95°C) to obtain the extract concentration of 5% (w/v). This experiment provides four treatments to rats within 15 days with five replicates for each treatment. The treatments for rats were K1 a positive control, K2 a negative control, K3 a healthy control, and P1 treated with leave infused water. The diabetic condition for K1, K2, and P1 was induced with an intravenous injection of 125 mg/kgBW alloxan monohydrate to the rats. After stable diabetic condition, K1 rats were treated with Glibenclamide (0,25 mg/kgBW), K2 rats were untreated, P1 rats were administered with leaves infused water of B. javanica (L) Merr 3 ml/day. K3 rats were uninduced and untreated. The hypoglycemic effect was observed by estimating the fasting blood glucose level of the rats every three days. After 15 days of treatments, P1 rats blood glucose level reduced by the 13,30%, while K1 rats 22,04%. The decrease in blood glucose level of both K1 and P1 rats have not reached the average blood glucose level of healthy rats. The result of the statistical analysis showed the infused extract effect was not significantly differed compared to positive control (P < 0.05).